Importance of gross motor skills in the physical activity of children aged 6 to 10 years - Quiroz Ávila, Joel (Revista Ecos de la Academia, 2024)
The development of gross motor skills at an early age is fundamental for establishing a solid base for sports practice, promoting an active life as well as healthy and happy growth in children. This study aims to highlight the importance of working on gross motor skills in children aged 6 to 10 years regarding their physical activity. The methodology used followed the Prisma protocol (Preferred Reporting Items for Systematic reviews and Meta-Analyses), collecting and analysing information from a variety of bibliographic sources, including databases such as Latindex, Redalyc, Dialnet and SciELO, as well as academic search engines such as Google Scholar and Worldwide Science. The results show that it is important to include gross motor skills in each physical activity session with variations in the time, frequency and intensity of the exercises. In addition, the use of support tools, such as motor games as well as leisure and recreational activities, is recommended to enhance learning. The findings underline the importance of working on gross motor skills in childhood; however, in practice, not always enough time and effort is invested to address it adequately.
Keywords: game; gross motor; movement; physical activity; physical education